2022
DOI: 10.22376/ijpbs/lpr.2022.12.3.l159-172
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Efficiency and Phytochemical Assessment of Stereospermum Chelonoides (L.F.) DC Flower and Leaf Mixed Powder Extracts

Abstract: Aim of the present study is to evaluate antibacterial efficiency of mixed powder preparation from the leaf and flower of Stereospermum chelonoides and its phytochemical evaluation. Bacterial species tested were isolated from UTI cases and showed multidrug resistance property. Stereospermum chelonoides is one of the medicinal trees worshiped as Holy plants in Thyagaraja Swamy Temple in Thiruvarur. It belongs to the family Bignoniaceae commonly called Sivappu Pathiri. All parts of the plant show a biological eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…As putative inducers, certain flavonoids including naringenin, luteolin, and quercetin exert effects on PPAR-γ activation and escalate insulin sensitivity ( Saini, 2010 ). Among the flavonoids, quercetin has the effects on relieving symptoms of diseases including high fever, eczema, asthma, and sinusitis ( Sreeram et al., 2021 ; Sangeetha et al., 2022 ). Epidemiological studies have shown that heart diseases are inversely related to flavonoid intake.…”
Section: Secondary Metabolitesmentioning
confidence: 99%
“…As putative inducers, certain flavonoids including naringenin, luteolin, and quercetin exert effects on PPAR-γ activation and escalate insulin sensitivity ( Saini, 2010 ). Among the flavonoids, quercetin has the effects on relieving symptoms of diseases including high fever, eczema, asthma, and sinusitis ( Sreeram et al., 2021 ; Sangeetha et al., 2022 ). Epidemiological studies have shown that heart diseases are inversely related to flavonoid intake.…”
Section: Secondary Metabolitesmentioning
confidence: 99%